Developing rotten institutions - Morgan Kelly (University College Dublin, Department of Economics, 2005)
This paper models corruption as optimal parasitism in organizations where teams of agents are weakly restrained by principals. Each agent takes on part of the role of principal, choosing how much to invest in policing to repress corruption in others and how rapaciously to act when unpoliced opportunities arise. This simple model incorporates most of the factors stressed in empirical analyses of corruption, and gives rise to a wide variety of equilibria. Allow income to co-evolve with corruption, we show how adding corruption to a textbook exogenous growth model leads to a Lucas paradox. When income and corruption a ect each other su ciently strongly, economies converge to two corner equilibria despite diminishing returns to capital: a rich, clean corner and a poor, corrupt one; a pattern that appears to characterize international data.
hdl:10197/949
Keywords: 330; Korruption; Bürokratie; Bürokratietheorie; Prinzipal-Agent-Theorie